TrackerSense : an entrepreneurial marketing start-up - O'Brien, Justin, (SAGE knowledge. Cases., 2016)
This entrepreneurial marketing case study focuses on serial entrepreneur Wayne Soutter and his current technology start-up TrackerSense, which produces a low-cost mobile tracking device for high-value packages.